Impact of vacuum freeze-drying on the reconstituted camel milk composition - TASTEMIROVA,Ukilim (2022)
Abstract In the dairy technology, for the preserving of initial nutritional properties of whole milk commonly a vacuum freeze-drying approach is used. However, a significant impact on the quality indicators of the resulting products within vacuum freeze-drying has a temperature of the product sublimation in the freeze-drying chamber. From the point of view of energy savings and maximum preservation of the initial qualities, the optimal sublimation temperature value is recommended at the t = -15 °C within vacuum freeze-drying process. The physicochemical indicators of whole and reconstituted camel milk have similar values within acceptable limits. Nevertheless, partial denaturation of amino acids that leading to the decreasing in the content of low molecular weight protein fractions and for the increasing of protein fractions with higher molecular weight are occurred. Thermolabile whey protein compounds, such as Albumin and Globulin fractions are especially susceptible to denaturation changes, due to the hydration membrane of proteins present on the surface is destroyed, leading to minor changes in the amino acid composition.